Fostering Productivity for Income Convergence in the Czech Republic - Fall, Falilou (OECD Economics Department Working Papers, 2017)
Over the past two decades, the income level of the Czech Republic has converged considerably towards the OECD average. However, after the 2008 global crisis, the convergence process stalled. Shortfalls in labour productivity have developed and are mainly structural. Policies are needed to foster domestic sources of productivity growth. Better targeting of government R&D support and more focused innovation policies that would be aided by a streamlining of policy institutions and interventions are necessary. In particular, tailored policies to increase knowledge-based capital (skills, management capacity, collaboration, etc.) are necessary to increase Czech firms' productivity. Also, resource reallocation should be facilitated by reforming framework conditions. In particular, bankruptcy rules, competition and regulation policies, access to finance and SME taxation need to be improved to boost SMEs' growth and productivity